(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
This paper provides a comprehensive review of the role of technology in shaping economic growth. It examines historical perspectives, theoretical frameworks, empirical evidence, current trends, challenges, opportunities, and future directions. The paper highlights the importance of technology in driving economic development, with a focus on digital technologies, artificial intelligence, sustainable technology, and globalization. It also discusses key challenges such as the digital divide, technological unemployment, and regulatory issues, along with opportunities for developing economies. The paper concludes with insights into future directions, including emerging technologies and their potential impact on economic growth.